The Use of Bamzle (Bamboe Puzzle) to Improve The Ability to Recognize Geometric Shape in Group A at TK Al-Ihlas Pasuruan (Kindergarten) - Ernawati, Ernawati; Kristiana, Dian; Rusdiani, Nurtina Irsad (Universitas Muhammadiyah Ponorogo, 2024)
This research aimed to improve the ability to recognize geometric shapes in group A at TK AL-Ihlas Pasuruan using the educational game tool Bamzle (Bamboe puzzle). Bamzle is an educational game tool created by the researchers made from bamboo, widely available in the TK Al-Ihlas school environment. This research is Classroom Action Research using the Kemis and Mc. Taggart's design model with four stages: planning, implementation, observation, and reflection. This research was carried out in 2 cycles, each with 2 meetings. The research subjects were children from group A, TK Al-Ihlas Kindergarten, Capang Village, Purwodadi District, Pasuruan Regency. Data collection techniques used were observation and documentation. The research results showed that the ability to recognize geometry increased from initial observation activities by 27%, then in Cycle I, it reached 41.67%, and in Cycle II, it reached 79.67%. The use of bamzle by teachers and students was very effective, as shown by the observations of the use of bamzle by students reaching 89% and by teachers reaching 92.7%. This has proved that Bamzle could improve the ability to recognize geometric shapes in group A at TK Al-Ihlas Pasuruan.